Strategi Harga,Kualitas Produk dan Kualitas Pelayanan Terhadap Keputusan Pembelian Bakso dan Mie Ayam Pakde Kembar ( Studi Dikantin Universitas Bhayangkara Jakarta Raya ) - Dian Suarditini; Dimas Anugrah; Fatimahtu Zahra; Fernando Imanuel Sitorus (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
Consumer satisfaction is a top priority in this study due to increasingly fierce competition between food stall industries. One way to create customer satisfaction at food stalls is to improve pricing strategies, service quality and product quality. If the food stall sets the right price, the quality and quality of the product is good, the consumer will be satisfied. With the appearance of satisfaction, consumers will come back to the store. The formulation of the problem in this study is whether there is a significant effect between price and customer satisfaction at Warung Kantin Bakso and Mie Ayam Pakde Kembar? Is there a significant influence between product quality and consumer satisfaction at Warung Makan Kantin Bakso and Mie Ayam Pakde Kembar? The method used in this research is quantitative and the type of research used is associative research.The results of this study indicate that the variable price, service quality and food stall product quality have a positive and significant effect on customer satisfaction partially. Meanwhile, from the simultaneous test results, there is a significant influence between price, service quality and product quality variables on consumer satisfaction. From the results of the determination test it is known that the adjusted R square value of customer satisfaction in food stalls is influenced by the independent variables, namely price, service quality and product quality, while the rest is explained by other variables outside the study.